MANAJEMEN SDM PESANTREN TMI PUTRI Al-AMIEN DALAM MENINGKATKAN WIBAWA DAN MORAL GURU - Dewi Fatimatus Zahro; Muru’atul Afifah (AL-BAYAN INSTITUTE, 2024)
This study aims to analyze HR management in enhancing teachers' authority and morale at TMI Putri Al-Amien Prenduan and to identify its supporting and inhibiting factors. The research employs a qualitative approach with a case study design. Data were collected through observation, semi-structured interviews, and documentation, then analyzed via data reduction, presentation, and conclusion drawing. Source triangulation was applied to ensure data validity. The study found that HR Management through transformational leadership significantly enhances teacher authority and morale. Human resource management (HRM) plays a crucial role in educational institutions, especially in boarding schools. Qualified human resources are essential for effectively managing various aspects of education. The implementation of proper HR management through transformational leadership can enhance teachers' authority and morale. However, challenges such as government policies and the emergence of new educational paradigms may impact teacher authority